FcGBP and VCAM-1 are ponderable biomarkers for differential diagnosis of alcoholic liver cirrhosis - Abassa, Kodjo-Kunale; Xiao, Xiu-Ping; Zhou, Hao-Xiong; Wu, Xiao-Ying; Guo, Yun-Wei; Wu, Bin (Drug and alcohol dependence, 2022)
Early diagnosis of alcoholic liver cirrhosis (ALD) and coexisting ALD and hepatitis B virus-induced cirrhosis (ALD+HBV) is primordial for an optimal management of these conditions. However, the lack of specific noninvasive biomarkers coupled with the inaccuracy of self-reported alcohol consumption make the early diagnosis of these pathologies difficult. This study aimed to identify biomarkers to diagnose ALD and differentiate ALD+HBV from HBV. Proteomics mass spectrometry technique was used to identify specific proteins of ALD by contrasting serums of ALD to that of healthy subjects. The accuracy of the selected proteins in diagnosing ALD and discriminating ALD+HBV from HBV was assessed in two independent cohorts using the area under the receiver operator characteristic curve (AUROC). 452 cirrhotic and normal subjects were enrolled in this study. The proteomic results revealed that FcGBP and VCAM-1 were the highest overexpressed proteins while comparing ALD samples to the healthy cohort. The combination of these two biomarkers had an AUROC of 0.986 (P < 0.001, sensitivity: 97.2%, specificity: 100%) in identifying ALD from the healthy cohort, and AUROC of 0.781 (P < 0.001, sensitivity: 81.8%, specificity: 77.0%) in differentiating ALD+HBV from HBV. This combination was more accurate than the combination of AST/ALT, MCV and GGT (ALD vs healthy, AUROC = 0.898; ALD+HBV vs HBV, AUROC = 0.599). The discrimination performance of this combination was further validated in another independent cohort. FcGBP and VCAM-1 are two promising biomarkers in the diagnosis of ALD and in the differentiating of ALD+HBV from HBV subjects. •ALD and ALD+HBV are often misdiagnosed due to inaccuracy of self-reported alcohol history.•Finding accurate diagnosis biomarkers for these pathologies will help in clinical practice.•This study found that FcFBP and VCAM-1 are potential biomarkers to diagnose ALD (AUROC=0.982) and ALD+HBV (AUROC=0.781).